Future ready : the four pathways to capturing digital value - Woerner, Stephanie L.; Weill, Peter; Sebastian, Ina M. (Boston, Massachusetts : Harvard Business Review Press, 2022)
"As the world continues to become more fully digitized, it seems like almost every company you can think of-including your own-has embarked on a "digital transformation" journey. The problem is, many companies start down the road without a good sense of where they are going or a clear idea of how they will create and capture digital value. Not surprisingly, this leads to problems: failure to realize the value from digital in their bottom lines, wasted resources and effort, added complexity and dysfunction. This compact, no-nonsense book provides a solution. In their years of working with senior executives around the world, MIT research scientists Stephanie Woerner, Peter Weill, and Ina Sebastian noticed that these leaders knew they had to transform their businesses, but lacked a coherent framework and a common language-a playbook-to guide and motivate their employees and keep everyone focused on a common goal. Future Ready is that playbook. Based on years of rigorous research with data from more than a thousand companies-BBVA, CEMEX, DBS, Fidelity, Maersk, and many others-the book provides a powerful, field-tested "four pathways" framework that offers insights into the important dimensions at which a firm must excel in order to be competitive, as well as the organizational disruptions that every firm must manage as part of the transformation journey. The book includes instructive examples, sharp analyses, assessments to help companies benchmark themselves against top performers, and many illuminating visuals to help crystallize the data and ideas. Woerner, Weill, and Sebastian show that the goal isn't digital transformation but rather a profound business transformation. Future Ready is your playbook for becoming a top performer in the digital economy"--
Introduction: Creating the Future Ready Firm -- :Four Pathways to Future Ready -- Pathway One: Industrialize first to... -- Pathway Two: Delight customers and... -- Pathway Three: Stairsteps to create incremental value -- Pathway Four: Create a new unit for... -- Leading the Transformation.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 15, 2023).
WorldCat record variable field(s) change: 050
Keywords: Organizational change; Success in business; Information technology -- Management; Business enterprises -- Technological innovations; Business enterprises -- Technological innovations; Information technology -- Management; Organizational change; Success in business; elektronické knihy; electronic books